2019
DOI: 10.3389/fpsyt.2019.00691
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Alpha Rhythm During Self-Referential Processing in Schizophrenia Patients

Abstract: Schizophrenia patients exhibited a psychological abnormal appearance when they recognized objects related to themselves. This cognitive process is associated with self-referential processing. In this study, the self-referential memory (SRM) task was performed by 18 schizophrenia patients and 18 healthy controls. In the encoding stage of the SRM task, the behavioral experiment data and electroencephalogram (EEG) data were recorded in three experimental conditions (self-referential condition, other-referential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Regarding the frequency and location domains, the results might be harmonious in the low-frequency range (alpha and theta), whereas they are not in the high-frequency range (beta and gamma). A general persistent finding in schizophrenia is reduced alpha power, especially in the resting-state, which might be linked to the increased state of arousal and abnormal self-referential processing [70,[72][73][74][75][76]. Delta and theta waves are mostly elevated [77][78][79], but only theta activity is decreased, especially in the frontal lobe [80], correlating with an impairment in working memory [81,82].…”
Section: Schizophreniamentioning
confidence: 99%
“…Regarding the frequency and location domains, the results might be harmonious in the low-frequency range (alpha and theta), whereas they are not in the high-frequency range (beta and gamma). A general persistent finding in schizophrenia is reduced alpha power, especially in the resting-state, which might be linked to the increased state of arousal and abnormal self-referential processing [70,[72][73][74][75][76]. Delta and theta waves are mostly elevated [77][78][79], but only theta activity is decreased, especially in the frontal lobe [80], correlating with an impairment in working memory [81,82].…”
Section: Schizophreniamentioning
confidence: 99%
“…Self-other integration was assessed with a social Simon task, a variant of the Simon task featuring an individual condition and a joint condition in which some stimuli are for one participant and some are for the other (24). For self-referential processing, studies used various tasks, for instance asking participants to judge whether adjectives (1) describe them, or (2) describe a person they know, and testing which group of adjectives they later remember better (25,26,30). Sensitivity to aberrant salience was measured through tasks such as an auditory oddball task (27,31).…”
Section: Paradigms or Tasks Probing The Self And Behavioral Datamentioning
confidence: 99%
“…The findings of studies investigating one or more individual frequency bands (22,23,25,35,43,44) are summarized in Figure 5 (excluding results from prestimulus or a resting state). In addition, Kim et al (16) found increased theta, alpha, and beta rest-task difference in subjects with schizophrenia in the posterior cingulate cortex, as well as decreased gamma resttask difference in the medial prefrontal cortex.…”
Section: Measures Of Brain Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations